ND ISOTOPE COMPOSITION OF EARLY CAMBRIAN DISCRETE BASINS - Felitsyn S.B.; Gubanov A.P. (My University, 2002)
A Nd isotope map of early Cambrian epeiric basins has been inferred from the Nd isotopic signature recorded in phosphatic Small Shelly Fossils. The most radiogenic [epsilon]Nd(t) values characterize water reservoirs along the Avalonian and Cadomian belts, while [epsilon]Nd(t) values of 20 were obtained in Laurentia and East Gondwanan Australia and China. Such a distribution of Nd isotope signatures results from the different provenance of early Cambrian epeiric seas: juvenile magmatic arcs and/or cordilleran for Mongolia, Siberia, Iberia and adjacent terranes, and cratonic sources for Laurentia and East Gondwana. Biogenic apatite of Small Shelly Fossils may be a useful tool for mapping of Nd isotope composition and documenting water mass exchange between discrete basins.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская